2016
DOI: 10.1080/15405702.2016.1153101
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic and cued immersion: Paratextual framing strategies on theDoctor WhoExperience Walking Tour

Abstract: Citation for final published version:Garner, Ross P. 2016. Symbolic and cued immersion: paratextual framing strategies on the Doctor Abstract:This article employs autoethnographic reflections to contribute towards debates concerning film-induced tourism (Beeton, 2005) by analysing the officially-endorsed Doctor Who Experience Walking Tour around filming locations from the BBC series in Cardiff Bay, Wales. Approaching this tour as an example of paratextuality (Gray, 2010), the article pursues two arguments. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Yet, unlike traditional forms of transmedia, the Rickmobile reveals a different type of fan docent. If, as previous research has shown, a tour docent creates a cued immersion for visitors (Garner 2016), then the fan docent highlights the relevant experience for other fans at a tourist location. Garner (2017) provides a reading of the docent, the tour guide, as a performative role for the fans in attendance (Lee 2012 describes a similar practice with Harry Potter tour guides).…”
Section: 'Look Where Being Smart Got Ya'mentioning
confidence: 94%
See 1 more Smart Citation
“…Yet, unlike traditional forms of transmedia, the Rickmobile reveals a different type of fan docent. If, as previous research has shown, a tour docent creates a cued immersion for visitors (Garner 2016), then the fan docent highlights the relevant experience for other fans at a tourist location. Garner (2017) provides a reading of the docent, the tour guide, as a performative role for the fans in attendance (Lee 2012 describes a similar practice with Harry Potter tour guides).…”
Section: 'Look Where Being Smart Got Ya'mentioning
confidence: 94%
“…The position of the fan docent in contemporary media tours is becoming more important, through both themed interaction with the guests as well as the cued immersion into the cult text (Garner 2016). Garner (2017)'s discussion of the tour guide reflects a changing perspective, from the docent as 'an unglamorous job' (Ap and Wong 2001, 556) to one where the docent represents a 'performed identity' of knowledge; here, the Rickmobile fans serve as tour guide for other fans (Garner 2017, 427).…”
Section: 'Look Where Being Smart Got Ya'mentioning
confidence: 99%
“…This more informal fan tourism allows for a looser and imaginative form of transmedia tourism and para-textualspatio play since 'underlying fantasies can operate in an unrestricted or loosely characteristic way, rather than being rigidly imposed' (Hills 2002, 149) by organised and more commercialised spaces. Rather than the trip being dictated by the stops on a walking or bus tour, and the 'reading' of locations preframed by tour guides (see Carl et al 2007, Garner 2016, I was free to make my own way through the city, choosing from the opportunities for different forms of transmedia fan-tourist activity and practice that this offered. Hills argues that 'Cult geographies […] sustain cult fans' fantasies of 'entering' into the cult text' (2002,151), but the ability to fully cross the imaginative line between 'reality' and the 'text' can be negatively impacted by factors such as a locations' lack of fidelity with the on-screen version, the behaviour of other visitors to the site, or disappointment with the commodification of a place.…”
Section: Para-textual-spatio Play and Unofficial Transmedia Tourismmentioning
confidence: 99%
“…Both Nick Couldry (2000, 83) and Melissa Beattie (2013, 179) note that visitors are required to 'cross through the screen' when entering into the diegesis of Coronation Street and Doctor Who; by playing clips prior to disembarking, fans on the Walking Dead tours were literally invited to '[cross] various thresholds' (Beattie 2013, 179) in order to enter the fictional frame. Despite Will Brooker's argument that outside spaces cannot 'offer a convincing experience of entering a fictional diegesis ' (2005, 14) the pairing of the fictional (via the TV clip) and the real (via leaving the bus) functioned as a form of 'cued immersion' (Garner 2016). Ross Garner argues that 'The [Doctor Who Experience Walking Tour] guide's script therefore imbues the location with diegetic and/or extra-diegetic significance through intertwining narrative and production discourses […] as the information disclosed provides cues which are designed …connect tour members to the space ' (2016, 93).…”
Section: 'The Landscape Has Forever Become Associated With the Undeadmentioning
confidence: 99%
“…Leshu Torchin's (2002) study of an unofficial tour of film and TV locations around New York demonstrates how 'the majority of [the] tour offers the deliberate display of discrepancy, or 'bloopers', which call attention to the gaps between virtual worlds and the world before us on the tour ' (2002, 254). Rather than cultivating a 'cued immersion' (Garner 2016) these anecdotes from guides seem to cue dissonance. Things such as pointing out how unlikely it would be for the characters on Friends (NBC 1994(NBC -2004 to be able to afford to rent in that area of New York given their jobs, or 'the practical impossibility of certain scenes' in Inspector Morse during the tour in Oxford (Reijinders 2010, 45) may add an air of authenticity to the transmedia tour, while simultaneously provoking a sense of dissonance from the storyworld.…”
Section: 'The Landscape Has Forever Become Associated With the Undeadmentioning
confidence: 99%